INOVASI MANAJEMEN PENGAJARAN DALAM PENINGKATAN PRESTASI SISWA KELAS X SMA IT SAMAWA CENDEKIAN KABUPATEN SUMBAWA TAHUN 2020 - Harjito (Jurnal TAMBORA, 2020)
This research is based on the condition of the impairment of student achievement vulnerability at the levelSenior High Schools due to curriculum changes over the past decade.The more role of educators (teachers) is needed, especially in terms of innovationteaching. So it is necessary to formulate the level of innovation effectivenessteaching management in improving the achievement of high school students in the Sumbawa area2020. The research method used is the type of qualitative appliedat the Samawa Cendekia Islamic Integrated High School for the 2019 academic year. As for the informantsin this study, namely the Deputy Principal of student affairs, teachers and students.The technique of collecting data is through interview, observation and documentation methods.Data analysis using interactive methods, data presentation, data reduction withChauvenet Criterion and generalized for conclusions. Related research resultsthe effectiveness of teaching management innovation in improving student achievement, namely innovationteaching is not in physical form but also in non-physical form by the teacher. Planningprogram in the development of potential teachers to create innovation inlearning. Management of institutional arrangements on the organizational structure,management, developing the potential of teachers in innovative ways through workshops,training, innovation training in teaching, so that it has a positive correlation with achievementstudents. The Principal of Schools supervises innovation management with teachersas well as regular supervision by the Supervisor from the District Education OfficeEvery month.